Techniques for assessing knee joint pain in arthritis - Fu Yu; Adwanikar Hita; Han Jeong S; Neugebauer Volker; Ji Guangchen (SAGE Publishing, 2007)
Abstract The assessment of pain is of critical importance for mechanistic studies as well as for the validation of drug targets. This review will focus on knee joint pain associated with arthritis. Different animal models have been developed for the study of knee joint arthritis. Behavioral tests in animal models of knee joint arthritis typically measure knee joint pain rather indirectly. In recent years, however, progress has been made in the development of tests that actually evaluate the sensitivity of the knee joint in arthritis models. They include measurements of the knee extension angle struggle threshold, hind limb withdrawal reflex threshold of knee compression force, and vocalizations in response to stimulation of the knee. A discussion of pain assessment in humans with arthritis pain conditions concludes this review.